Parasol against the axe - Oyeyemi, Helen (Riverhead Books, 2024)
For reasons of her own, Hero Tojosoa accepts an invitation she was half expected to decline, and finds herself in Prague on a bachelorette weekend hosted by her estranged friend Sofie. Little does she know she's arrived in a city with a penchant for playing tricks on the unsuspecting. A book Hero has brought with her seems to be warping her mind: the text changes depending on when it's being read and who's doing the reading, revealing startling new stories of fictional Praguers past and present. Uninvited companions appear at bachelorette activities and at city landmarks, offering opinions, humor, and even a taste of treachery. When a third woman from Hero and Sofie's past appears unexpectedly, the tensions between the friends' different accounts of the past reach a new level.